Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd003794.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Combined corticosteroid and long-acting beta-agonist in one inhaler versus placebo for chronic obstructive pulmonary disease

Abstract: Compared with placebo, combination therapy led to a significant reduction of a quarter in exacerbation rates. There was a significant reduction in all-cause mortality with the addition of data from the TORCH trial. The increased risk of pneumonia is a concern, and better reporting of this outcome in future studies would be helpful. In order to draw firmer conclusions about the effects of combination therapy in a single inhaler more data are necessary, particularly in relation to the profile of adverse events a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 68 publications
1
76
1
4
Order By: Relevance
“…In this study, both the inhaled steroid-containing arms were associated with increased incidence of pneumonia, with a doubling of the incidence in the combination arm from 4 to 8% over the 3-yr period. A meta-analysis of 11 studies of combination preparations (fluticasone/salmeterol and budesonide/formoterol) has confirmed these findings, with an OR 1.83 (95% CI 1.51-2.21) increase in the overall risk for pneumonia attributed to the combination treatment [34]. In a retrospective database analysis, the effect appeared to be dose-related, with doses .1,000 mcg?day -1 of beclomethasone equivalent more likely to be linked to pneumonia than lower doses.…”
Section: Community-acquired Pneumonia In Copdmentioning
confidence: 81%
“…In this study, both the inhaled steroid-containing arms were associated with increased incidence of pneumonia, with a doubling of the incidence in the combination arm from 4 to 8% over the 3-yr period. A meta-analysis of 11 studies of combination preparations (fluticasone/salmeterol and budesonide/formoterol) has confirmed these findings, with an OR 1.83 (95% CI 1.51-2.21) increase in the overall risk for pneumonia attributed to the combination treatment [34]. In a retrospective database analysis, the effect appeared to be dose-related, with doses .1,000 mcg?day -1 of beclomethasone equivalent more likely to be linked to pneumonia than lower doses.…”
Section: Community-acquired Pneumonia In Copdmentioning
confidence: 81%
“…The 393 study observed a relative reduction in mortality of 17% over three years for patients receiving 394 SLM/FP, although this just failed to reach statistical significance. A subsequent Cochrane review 395 observed survival benefits with combination therapy compared both to placebo (34) and to ICS 396 alone (14). In vivo studies using bronchial biopsies have generated further supporting evidence 397 for complementary interactions between LABAs and corticosteroids on airway inflammation and 398 pathology in COPD patients (18,19).…”
Section: Usmani 18mentioning
confidence: 99%
“…10 Any benefits come at the cost of an increased risk of pneumonia as well as oral candidiasis, voice hoarseness and skin bruising. 19,20 However, this patient only has a moderate obstructive defect so if significant dyspnoea persists in spite of the above suggestions, further assessment at a specialist respiratory clinic may be warranted. This would allow full lung function tests to be performed including gas transfer and lung volumes (that are not routinely available in primary care), and further assessment with CT scans which in specific clinical situations may lead to some of the newer treatments including lung volume reduction therapy.…”
Section: Pharmacological Managementmentioning
confidence: 97%